1995
DOI: 10.1002/j.1460-2075.1995.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere elongation in immortal human cells without detectable telomerase activity.

Abstract: Immortalization of human cells is often associated with reactivation of telomerase, a ribonucleoprotein enzyme that adds TTAGGG repeats onto telomeres and compensates for their shortening. We examined whether telomerase activation is necessary for immortalization. All normal human fibroblasts tested were negative for telomerase activity. Thirteen out of 13 DNA tumor virus‐transformed cell cultures were also negative in the pre‐crisis (i.e. non‐immortalized) stage. Of 35 immortalized cell lines, 20 had telomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
878
2
16

Year Published

1996
1996
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,165 publications
(926 citation statements)
references
References 38 publications
30
878
2
16
Order By: Relevance
“…In contrast, when IL-2 dependent cells were deprived of IL-2, expression levels of both Bcl-2 and telomerase were reduced. There is further evidence that the mere presence of telomerase may not be essential for immortality (Bryan et al, 1995) since somatic cell hybrids between telomerase positive cells and telomerase-negative cells usually show that senescence is dominant over the malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when IL-2 dependent cells were deprived of IL-2, expression levels of both Bcl-2 and telomerase were reduced. There is further evidence that the mere presence of telomerase may not be essential for immortality (Bryan et al, 1995) since somatic cell hybrids between telomerase positive cells and telomerase-negative cells usually show that senescence is dominant over the malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Langford et al (1995) found that some anaplastic astrocytomas with malignant potential showed no telomerase activity and suspected an alternative mechanism of maintaining telomere length. Bryan et al (1995) recently described a telomerase-independent mechanism in an immortalized human cell line without detectable telomerase activity. The third reason relates to the sensitivity of our assay.…”
Section: Qualitative Telomerase Activitymentioning
confidence: 99%
“…The initial telomerase extension reaction and the secondary PCR reaction were performed in di erent tubes. A phenolchloroform extraction of the telomerase-extended product was used to eliminate potential inhibitors of the secondary PCR reaction (Bryan et al, 1995). The telomerase extension reaction was performed at room temperature for 30 min.…”
Section: Telomerase Assaymentioning
confidence: 99%
“…Consequently, telomerase expession has been proposed to be required for cellular immortalization . However, other mechanisms of telomere maintenance are also possible (Bryan et al, 1995;Strahl and Blackburn, 1996), such as recombinational events as seen in yeast (Wang and Zakian, 1990) or transposition of retrotransposons as found in Drosophila (Beissmann and Mason, 1992; Levis et al, 1993). Alterations in the regulation of telomerase expression may play a critical role in the immortalization stage of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%